Microstructure-modified proton exchange membranes for high-performance direct methanol fuel cells. (15th September 2017) - Wang, Manxiang; Liu, Guicheng; Tian, Zhe; Shao, Yingna; Wang, Lei; Ye, Feng; Tran, Minh Xuan; Yun, Yanbin; Lee, Joong Kee
Highlights: A simple hot-mould-modified Nafion membrane is used for direct methanol fuel cells. Regular spindle-type groove array is uniformly distributed on the membrane surface. Modification lowers methanol crossover, swelling, and improves proton conductivity. Power density and long-time running performance of fuel cells are improved visibly. This method provides a practicable way for direct methanol fuel cell applications. Abstract: To lower methanol crossover and volume swelling degree, and to improve proton conductivity, a simple hot-mould-modifying method has been introduced to modify Nafion membrane for the direct methanol fuel cell application. To evaluate effect of the modification on properties of the Nafion membrane and fuel cell performance, a series of measurements of membranes and fuel cells have been carried out. The results show that, compared with the normal membrane, the modified Nafion membrane with regular spindle-type groove array possesses higher proton conductivity and methanol diffusion resistance, and 31.9% better dimensional stability, owing to its larger electrical double-layer capacitance come from the higher contact area between electron-electrode and ion electrolyte, and its more compact internal structure. And also, the direct methanol fuel cell based on the modified Nafion membrane shows 13.3% higher discharge power density and better long-time running performance than the normal one. Furthermore, this hot-mould-modifying method could be introduced into doping/coating-modified membranes reported in the current literature to further modify Nafion membranes, because this method is compatible with the current modifications.